A genome-wide RNAi screen reveals MAP kinase phosphatases as key ERK pathway regulators during embryonic stem cell differentiation. - Shen-Hsi Yang (PLoS Genetics, 2012)
Embryonic stem cells and induced pluripotent stem cells represent potentially important therapeutic agents in regenerative medicine. Complex interlinked transcriptional and signaling networks control the fate of these cells towards maintenance of pluripotency or differentiation. In this study we have focused on how mouse embryonic stem cells begin to differentiate and lose pluripotency and, in particular, the role that the ERK MAP kinase and GSK3 signaling pathways play in this process. Through a genome-wide siRNA screen we have identified more than 400 genes involved in loss of pluripotency and promoting the onset of differentiation. These genes were functionally associated with the ERK and/or GSK3 pathways, providing an important resource for studying the roles of these pathways in controlling escape from the pluripotent ground state. More detailed analysis identified MAP kinase phosphatases as a focal point of regulation and demonstrated an important role for these enzymes in controlling ERK activation kinetics and subsequently determining early embryonic stem cell fate decisions.